DEVELOPMENT OF CREATIVE POTENTIAL OF FUTURE TEACHERS BY MEANS OF IMPLEMENTATION OF PEDAGOGICAL TECHNOLOGIES - A.K. Zychkov (Academy of Cognitive and Natural Sciences, 2010)
The question of professional preparation of future teacher, development of his creative potential by facilities of introduction of pedagogical technologies rises in the real article.